Prohibición de rendir caución, en los delitos cuya pena máxima privativa de libertad sea superior a cinco años, vulnera el derecho a la libertad ambulatoria del procesado - Islam García, Williams Geovanny (2023)
Through this titling project, it is proposed to expose the effects of numeral 2 of article 544 of the Comprehensive Criminal Organic Code (hereinafter COIP), a regulation that prevents the application of the bond as a mechanism by which the effects of imprisonment are suspended. preventive, in those criminal types whose prison sentence is greater than five years. Regulated in article 543 of the COIP, the surety is a guarantee for those cases in which a preventive detention order has been issued to guarantee the appearance of the defendant in court. It should be noted that the precautionary measure of pretrial detention, as stated by the InterAmerican Court of Human Rights, must be constantly reviewed. Not only because it is a precautionary measure of a personal nature that limits the enjoyment of a fundamental right such as the Right to freedom of movement, but also to achieve control of arbitrariness and illegality at the time such measure is granted..........